2019
DOI: 10.1001/jamanetworkopen.2019.6928
|View full text |Cite
|
Sign up to set email alerts
|

Access to Primary Care Clinics for Patients With Chronic Pain Receiving Opioids

Abstract: IMPORTANCE Opioid-prescribing policies and guidelines aimed at reducing inappropriate opioid prescribing may lead physicians to stop prescribing opioids. Patients may thus encounter difficulties finding primary care practitioners willing to care for them if they take opioids. OBJECTIVES To assess practitioner willingness to accept and continue prescribing opioids to new patients with pain and whether this willingness differs across payer types. DESIGN, SETTING, AND PARTICIPANTS This survey study used a simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 28 publications
0
82
1
Order By: Relevance
“…It is notable that yearly state-level opioid prescribing rates were associated with fewer opioid overdose deaths in the final model, potentially reflecting the evolving nature of the opioid crisis in which illicit and synthetic opioids are being abused. 1,2 The current study suggests that regional variation in anger regulation is an important cultural backdrop for understanding why opioids are misused.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is notable that yearly state-level opioid prescribing rates were associated with fewer opioid overdose deaths in the final model, potentially reflecting the evolving nature of the opioid crisis in which illicit and synthetic opioids are being abused. 1,2 The current study suggests that regional variation in anger regulation is an important cultural backdrop for understanding why opioids are misused.…”
Section: Discussionmentioning
confidence: 86%
“…1 Surveys suggest that a number of clinicians do not accept new patients who use opioids in an effort to avoid patient risks and professional liability. 2 In contrast, palliative care clinicians specialize in treating painful conditions with complex etiologies that may require opioid therapies. Opioid misuse is common, and even when used as prescribed many patients develop symptoms of tolerance and withdrawal.…”
mentioning
confidence: 99%
“…Sequential papers in 2019 showed: (a) that most discontinuation among high dose Medicaid patients in Vermont was rapid, and often followed by hospital care; 56 (b) that cessation was associated with increased risk of death from overdose in one health system, 57 and termination of care relationships in another; 58 (c) that upward and downward dose variations were associated with elevated overdose risk in Colorado; 59 (d) that physicians reduce doses rapidly in ways that exceed CDC Guidelines among one in four patients; 60 (e) that prescription opioid cessation among veterans was followed by elevated risk of death from both overdose and suicide, in analyses that controlled for a range of patient characteristics. 61 Finally, a Michigan study found that 41% of primary care physicians refuse to see patients already receiving opioids, 62 a situation that limits the opportunities to protect the same patients.…”
Section: Taper: Evidence For Benefitmentioning
confidence: 99%
“… 13 Authors of a study of mortality after discontinuation of opioid therapy suggested that these deaths could reflect interruption of other medical care, loss of tolerance, or destabilisation of an underlying opioid use disorder. 14 Primary care is well-placed to manage substance use disorder, but without support many GPs are reluctant to take on new patients being treated with opioids 15 or to prescribe opioid substitution therapy. 16 They may indiscriminately discharge patients with problems identified by real-time prescription monitoring from their practice.…”
Section: Real-time Prescription Monitoringmentioning
confidence: 99%